Human activity suggested by the taphonomy of 60 ka and 50 ka faunal remains from Sibudu Cave - Cain, C. R. (Southern African Humanities, 2021)
A taphonomic study of a full range of faunal specimens from selected layers in the Middle Stone Age (MSA) reveals that the non-human contribution was minimal in Sibudu Cave. Human signatures are abundant in the form of carcass processing, human-related burning and post-depositional modification on bone. Comparison with other MSA assemblages from southern Africa shows that the Sibudu material is unusual. Thus work is still needed to understand animal acquisition and disposal at ~60 ka and ~50 ka. To cite this article: Cain, C. R. 2006. Human activity suggested by the taphonomy of 60 ka and 50 ka faunal remains from Sibudu Cave. Southern African Humanities 18 (1): 241-60.